A conceptual framework to assess the impact of training on equipment cost and availability in the military context - Rodrigues, Duarte; Erkoyuncu, John Ahmet; Starr, Andrew G.; Wilding, Stephen; Dibble, Alan; Laity, Martin; Owen, Richard (Elsevier, 2015)
Designing military support is challenging and current practices need to be reviewed and improved. This paper gives an overview of the Industry current practices in designing military support under Ministry of Defence/Industry agreements (in particular for Contracting for Availability (CfA)), and identifies challenges and opportunities for improvement. E.g. training delivery was identified as an important opportunity for improving the CfA in-service phase. Thus, an innovative conceptual framework is presented to assess the impact of training on the equipment availability and cost. Additionally, guidelines for improving the current training delivery strategies are presented, which can also be applied to other Industry contexts.
In: 4th International Conference on Through-Life Engineering Services, 3-4 November 2015, Cranfield University, Cranfield, UK.
Keywords: Availability Contracts; Support Design; Training; Equipment Availability; Cost